STAT3 Mediates the Differential Effects of Oncostatin M and TNFα on RA Synovial Fibroblast and Endothelial Cell Function - Hanlon, Megan M.; Rakovich, Tatsiana; Cunningham, Clare C.; Ansboro, Sharon; Veale, Douglas J.; Fearon, Ursula; McGarry, Trudy (Frontiers in Immunology, 2019)
Objectives: Oncostatin M (OSM), a pleiotropic cytokine and a member of the gp130/IL-6 cytokine family, has been implicated in the pathogenesis of autoimmune diseases. Here we investigate the mechanisms by which its synergistic interactions with TNFα regulate the cellular bioenergetics and invasive function of synovial cells from patients with Rheumatoid Arthritis. Methods: Primary RA synovial fibroblasts (RAFLS) and human umbilical vein endothelial cells (HUVEC) were cultured with OSM alone or in combination with TNFα. Pro-inflammatory cytokines, angiogenic growth factors and adhesion molecules were quantified by real-time PCR and ELISA. Invasion, angiogenesis and cellular adhesion were quantified by Transwell invasion chambers, Matrigel tube formation assays, and adhesion binding assays. Cellular bioenergetics was assessed using the Seahorse XFe96 Analyser. Key metabolic genes (GLUT-1, HK2, PFKFB3, HIF1α, LDHA, PKM2) and transcription factor STAT3 were measured using real-time PCR and western blot. Results: OSM differentially regulates pro-inflammatory mediators in RAFLS and HUVEC, with IL-6, MCP-1, ICAM-1 and VEGF all significantly induced, in contrast to the observed inhibition of IL-8 and GROα, with opposing effects observed for VCAM-1 depending on cell type. Functionally, OSM significantly induced angiogenic network formation, adhesion and invasive mechanisms. This was accompanied by a change in the cellular bioenergetic profile of the cells, where OSM significantly increased the ECAR/OCR ratio in favour of glycolysis, paralleled by induction of the glucose transporter GLUT-1 and key glycolytic enzymes (HK2, PFKFB3, HIF1α). OSM synergises with TNFα to differentially regulate pro-inflammatory mechanisms in RAFLS and HUVEC. Interestingly, OSM differentially synergises with TNFα to regulate metabolic reprogramming, where induction of glycolytic activity with concomitant attenuation of mitochondrial respiration and ATP activity was demonstrated in RAFLS but not in HUVEC. Finally, we identified a mechanism, whereby the combination of OSM with TNFα induces transcriptional activity of STAT3 only in RAFLS, with no effect observed in HUVEC. Conclusion: STAT3 mediates the differential effects of OSM and TNFα on RAFLS and EC function. Targeting OSM or downstream signalling pathways may lead to new potential therapeutic or adjuvant strategies, particularly for those patients who have sub-optimal responses to TNFi.